NERINT STRATEGIC ANALYSIS - Visentini, Paulo; Pereira, Analúcia; Ianhez, Rodrigo; Martins, José Miguel Quedi; Magno, Bruno; Thudium, Guilherme; Ribeiro, Erik; Pecequilo, Cristina; Granato, Leonardo (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The acceleration of pace of international events and processes requires qualified analysis beyond the political-journalistic bias that often characterises most interpretations of contemporary matters. Thus, in addition to theoretical-analytical articles, publishing a brief evaluation of critical current events was imperative. To this end, the Brazilian Centre for Strategy and International Relations (NERINT/UFRGS), a member of the Centre for International Studies on Government (CEGOV/UFRGS), launched the NERINT Strategic Analysis series, with the contribution of its specialised researchers and guests with thematic expertise, which will be published at the end of every issue of AUSTRAL: Brazilian Journal of Strategy and International Relations.